2011
DOI: 10.5009/gnl.2011.5.4.472
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lifestyle Modification on Symptoms and Quality of Life in Patients with Irritable Bowel Syndrome: A Prospective Observational Study

Abstract: Background/AimsAlthough notably common, irritable bowel syndrome (IBS) has no specific cure. Lifestyle modification may be as important as medication; however, few studies support the effectiveness of such modifications. We performed this observational study of IBS patients to explore further the role of lifestyle changes in treatment.MethodsThis study included 831 men who enlisted in 2010 as armed surgeon cadets and 85 women who concurrently entered the Armed Forces Nursing Academy. Of these 916 participants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
(20 reference statements)
4
21
0
1
Order By: Relevance
“…When performing subgroup analyses, gastrointestinal symptoms were improved by moderate physical activity in the MC1 group, in accordance with previous studies describing improvement of IBS symptoms after training [13]. However, these results may be interpreted 16 with caution, as they may reflect that women with more severe disease are not able to exercise, but have to stay at home, close to the toilet.…”
Section: Patients With Irritable Bowel Syndromesupporting
confidence: 88%
See 2 more Smart Citations
“…When performing subgroup analyses, gastrointestinal symptoms were improved by moderate physical activity in the MC1 group, in accordance with previous studies describing improvement of IBS symptoms after training [13]. However, these results may be interpreted 16 with caution, as they may reflect that women with more severe disease are not able to exercise, but have to stay at home, close to the toilet.…”
Section: Patients With Irritable Bowel Syndromesupporting
confidence: 88%
“…Life style factors such us smoking, drinking and physical activity may be of importance, since these factors affect the gastrointestinal tract, psychological well-being, and HRQOL [12,13,14]. Smoking is a known risk factor for developing MC [15], but its effect on symptoms when the disease is present has never been examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of patients with IBS undergoing military training, 62.9% of patients had improvement from baseline in bowel habits after 9 weeks of lifestyle modification imposed by the training (i.e. no smoking or alcohol consumption, regular meals, physical activity) [Kang et al 2011]. After 9 weeks of training, mean stool frequency decreased from baseline, and the percentage of patients with normal stools (defined as Bristol stool scale score of 3, 4, or 5) increased from baseline (p = 0.05).…”
Section: Management Of Ibs: Established Approachesmentioning
confidence: 99%
“…Few studies have already reported long term effects of hypnotherapy [9]. Quality of life and symptoms decreased significantly in 63% of the participants after military training [16]. Pain was relieved in patients after 7-12 sessions of hypnotherapy [17].…”
mentioning
confidence: 99%